Induced chorioretinal venous anastomosis in experimental retinal branch vein occlusion. Issue 10 (October 1992) - McAllister, I L; Yu, D Y; Vijayasekaran, S; Barry, C; Constable, I
Abstract : Iatrogenic retinal vein to choroidal vein anastomoses were created using laser photocoagulation in six of seven dog eyes in which a partial branch retinal vein occlusion had previously been created photochemically. A similar attempt to create an anastomosis was made in six control eyes in which no branch vein occlusion was present. In the eyes in which a branch retinal vein had been created, a venous chorioretinal anastomosis appeared to be present by 3 to 6 weeks. In three control eyes similar venous anastomosis was created; however this took 6 to 8 weeks to develop and was of much smaller calibre than the one that developed in the presence of a partial branch retinal vein occlusion. No adverse complications were noted in the period of the study (3 months). This study demonstrates that chorioretinal venous anastomoses can be created and may be of use in the treatment of partial retinal vein occlusions that show signs of progression.